Oral Feeding Competences of Healthy Preterm Infants: A Review - N. Bertoncelli; G. Cuomo; S. Cattani; C. Mazzi; M. Pugliese; E. Coccolini; P. Zagni; B. Mordini; F. Ferrari (International Journal of Pediatrics)
Background. With increasing sophistication and technology, survival rates hugely improved among preterm infants admitted to the neonatal intensive care unit. Nutrition and feeding remain a challenge and preterm infants are at high risk of encountering oral feeding difficulties. Objective. To determine what facts may impact on oral feeding readiness and competence and which kind of interventions should enhance oral feeding performance in preterm infants. Search Strategy. MEDILINE database was explored and articles relevant to this topic were collected starting from 2009 up to 2011. Main Results. Increasingly robust alertness prior to and during feeding does positively impact the infant’s feeding Skills. The review found that oral and non-oral sensorimotor interventions, provided singly or in combination, shortened the transition time to independent oral feeding in preterm infants and that preterm infants who received a combined oral and sensorimotor intervention demonstrated more advanced nutritive sucking, suck-swallow and swallow-respiration coordination than those who received an oral or sensorimotor intervention singly.